Utilization of Activated Charcoal from Cassava Peel and Straw in Reducing Cadmium Levels in Putri Cempo Landfill Leachate - Hasna Nadia Hikari; Lathifa Putri Wiedhya Syahrani; Luthfia Luthfia; Sofiyana Khoirunnisa; Siti Rachmawati (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Contamination of leachate due to excessive rainwater infiltration into landfill sites presents a significant environmental and public health concern. This study aims to address the adverse impacts of cadmium (Cd) pollution in leachate, specifically its risks to human health and the environment. To address this issue, the research investigates the use of natural adsorbents to mitigate agricultural waste. Straw and cassava peel, abundantly available in Indonesia due to the country's substantial rice and cassava production, were selected as potential adsorbents. The findings of this study are important for guiding pollution control measures and evaluating community activities near pollution sources, particularly focusing on Cd pollution originating from Putri Cempo in Jatirejo Village, Mojosongo, Jebres, Surakarta. The research shows that cassava peel waste is highly effective in adsorbing cadmium metal levels in leachate, with a significant total effectiveness (EF%) rating of 0.3144. Additionally, the study identifies the optimal burning temperature for activated charcoal derived from cassava peel as 600°C, resulting in the highest EF% value of 0.515152.